Afiksasi Pembentukan Verba dalam Bahasa Indonesia Ragam Informal pada Webtoon yang Berjudul “Ngopi, Yuk!” - Sari, Dini Gilang; Fasya, Mahmud (Crises on Languages and Literature, 2024)
There is a unique structure in every language. The existence of unique languages comes from the study of language diversity. This study focuses on the use of verb formation affixes in informal Indonesian. The data for this study comes from a comic entitled “Ngopi, yuk!” by Assyifa S. Arum and Romy Hernadi on Webtoon. The data in this study is limited to the first 15 episodes. The results of this study indicate that there are five verb formation affixes which include (1) the prefixes me-, di-, ber-, ke-, ter-, per-, and nge-; (2) the suffixes -in, -an, and -kan; (3) the confix ke-an; (4) the simulfix N-; and (5) the combination of the affixes N-in, di-in, memper-kan, di-kan, and me-kan. In addition, the verb formation affixes in informal Indonesian on Webtoon entitled “Ngopi, yuk!” dominantly use the morpheme -in and the morpheme N-, namely, nine data and eight data.